Answer:
read step by step
Step-by-step explanation:
.10×55.86 = 5.58
then subtract $5.58 from your total .
and that will give you the answer
Answer:
x =
7
Step-by-step explanation:
= 49
can equal 7 or -7
7 x 7 = 49. -7 x -7 = 49
Answer:
4√(xy³)
Step-by-step explanation:
8√(x²y⁶)
The above expression can be simplified as follow:
8√(x²y⁶)
Recall:
m√a = a^1/m
Therefore,
8√(x²y⁶) = (x²y⁶)^1/8
Recall:
(aⁿ)^1/m = a^(n/m)
Therefore,
(x²y⁶)^1/8 = x^(2/8)•y^(6/8)
= x^1/4•y^3/4
= (xy³)^1/4
Recall :
a^1/m = m√a
Therefore,
(xy³)^1/4 = 4√(xy³)
Therefore,
8√(x²y⁶) = 4√(xy³)
Answer:
-1/7 y + 1/7 x
Step-by-step explanation:
Can also be written as
1/7 x - 1/7 y